2018
DOI: 10.29136/mediterranean.408097
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on survival rate and growth characteristics of pure hair goat and Saanen x hair goat (F1, B1, B2) crossbreds in breeder conditions

Abstract: Bu araştırma, Saanen x Kıl (S x K) keçi genotipleri (F1, G1 ve G2) ve Kıl keçilerinde büyüme ve yaşama gücünü ve etkili faktörleri tespit etmek amacıyla yapılmıştır. Çalışma, Amasya ili Sarılar köyünde özel bir işletmede yetiştirilen 24 baş S x K F1, 91 baş S x K G1, 14 baş S x K G2 ve 53 baş Kıl keçisi oğlakları ile yürütülmüştür. Oğlakların doğum, 1 ay, 2.5 ay ve 6 ay canlı ağırlıkları üzerine genotip, doğum tipi ve cinsiyetin etkisi önemli (P<0.05) bulunmuştur. Ana yaşının oğlakların doğum ve 2.5 ay canlı a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…In this study, the birth weight and 2 nd -month live weight of Kilis kids were found to be lower than in previous studies on Kilis kids in the original breeding area (Keskin et al, 2017;Özdemir and Keskin, 2018;Gül et al, 2022;Keskin et al, 2022). However, live weights of Kilis kids from birth to 6 months of age were lower, but partly similar, than those of native gene resources, pure and crossbred Hair kid genotypes (Erduran, 2017;Çelik and Olfaz, 2018;Akbaş et al, 2023). It is seen that environmental factors significantly affect the live weight and growth characteristics of Kilis kids from birth to one year of age.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…In this study, the birth weight and 2 nd -month live weight of Kilis kids were found to be lower than in previous studies on Kilis kids in the original breeding area (Keskin et al, 2017;Özdemir and Keskin, 2018;Gül et al, 2022;Keskin et al, 2022). However, live weights of Kilis kids from birth to 6 months of age were lower, but partly similar, than those of native gene resources, pure and crossbred Hair kid genotypes (Erduran, 2017;Çelik and Olfaz, 2018;Akbaş et al, 2023). It is seen that environmental factors significantly affect the live weight and growth characteristics of Kilis kids from birth to one year of age.…”
Section: Resultscontrasting
confidence: 66%
“…The first scientific researches on the development of dairy goat breeding in Türkiye mainly focused on the Aegean, Mediterranean and Marmara regions (Şengonca et al, 2003;Tölü, 2010;Erduran, 2017;Keskin et al, 2017). However, in recent decades, it has also been intensified in Central Anatolia and Central Black Sea regions (Çelik and Olfaz, 2018;Erduran, 2022Erduran, , 2023a. In these studies, Alpine and Saanen breeds, which are exotic dairy breeds, and Kilis and Malta breeds, which are domestic dairy breeds, have been used primarily.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, Hair goat kids have been shown to perform better than Saanen × Hair (F1) kids in terms of growth characteristics Gökdal et al, 2013). Some studies did not find statistical differences in the growth characteristics of Saanen × Hair and Hair goats (Ekiz et al, 2014;Atay, 2016;Çelik & Olfaz, 2018). The study of Şengonca et al (2002) reported that crossbred kids performed better than Hair kids.…”
Section: Resultsmentioning
confidence: 99%
“…Growth refers to the weight gains in animals due to biological events that generally take place directly proportional to age. Growth is a process that begins in the embryonic stage and continues until the mature age (Tozlu Çelik and Olfaz, 2018). Different mathematical methods have been used to define growth.…”
Section: Introductionmentioning
confidence: 99%